Utopia atbp: Versions of the Ideal in Philippine Fiction - Groyon, Vicente Garcia (Archīum Ateneo, 2017)
In Utopia, Thomas More delivers a specific and context-bound critique of Tudor England through a faux anthropological report on a perfect society, “perfect” being defined as everything that Tudor England was not. Philippine fiction can similarly be read as visions of what the nation could and should be, delivered in oblique flashes that project a fragmentary composite picture of everything that the Philippines is not, or no longer is. The supposedly opposed vectors of romance and realism coincide in their explicit and implicit yearnings for contentment and happiness, echoing More’s own bemused, amused impatience with his flawed country. Through a telescoped survey of Philippine fiction in English, this article traces the contours of the Philippine utopian ideal.